Corporate governance bundles and earnings management: The role of audit committees and ownership concentration - Kunsrison, Rotcharin (Kasetsart Journal of Social Sciences, 2026)
Drawing on the notion of governance bundles, this study aims to verify whether governance mechanisms are interrelated and reveal the interaction mechanisms between firm-level governance. By using a unique dataset from Thailand with 1,364 firm-year observations from years 2017–2020 and moderating regression as a research tool, the findings indicate that a larger audit committee is necessary for firms with concentrated ownership to offset the power of controlling shareholder over earnings management. Theoretically, the findings ensure that corporate governance within the firm functions collectively as a bundle. In addition, the findings challenge the existing regulations in a way that audit committee size should not be standardized for all types of firms. Instead, the size of such a committee should vary depending on the degree of ownership concentration.